Literature Review: Bioactivity of Alkaloids from Various Plants that Have Potential as Antibacterials - Usman; Hutauruk, Kevin Jeremia; Rabiah, Nasya Hikmatul; Rahmadani, Intan Aulia; Miranda, Esti (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Alkaloid compounds are active secondary metabolite compounds produced by plants. These alkaloid compounds provide extraordinary health benefits for humans because alkaloid compounds are efficacious as antidiarrheal, anti-microbial, anti-diabetic, anti-microbial, and anti-malarial. The purpose of this literature review is to describe plants that produce alkaloid compounds as secondary metabolites and their bioactivity as antimicrobials. This literature-based study was systematically carried out to gather, evaluate, and synthesize research results concerning the antibacterial properties of alkaloids and other natural secondary metabolites from plants. The analysis focused on publications from 2015 to 2025, sourced through a structured search in the Medline database using PubMed and Google Scholar. The results of this literature review explain that there are many plants that produce alkaloid compounds as their secondary metabolites. Alkaloid compounds in each plant have the same bioactivity both as anti-fungal and anti-fungal. Alkaloids in their bioactivity will interfere with and damage cell formation in microbes so that microbial growth will be inhibited.